Tracing The Five Stages of Freytag's Pyramid in The Opera Batak Toba Sipiso Somalim - Naomi Suryana Manurung; Sondang Manik; Zubil Ezer Sihite (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2026)
This study aims to analyze the narrative structure of the Batak Toba Opera Sipiso Somalim by applying Gustav Freytag's Pyramid, thereby addressing the scarcity of structural literary analysis on Indonesian traditional performing arts. Employing a descriptive qualitative method with a narrative analysis approach, this research deconstructs the opera's plot based on its documented script and performance recordings. The analysis systematically classifies narrative events into Freytag's five stages: exposition, rising action, climax, falling action, and resolution, followed by an interpretive analysis of their cultural significance. The findings reveal that Sipiso Somalim adheres closely to the pyramidal structure. The exposition establishes the Batak Toba adat (customary law) and social order. The rising action intensifies through the protagonist's internal conflict between individual desire and communal obligations. The climax is marked by an irreversible decision that violates adat, leading to tragic consequences in the falling action. The resolution restores social equilibrium, albeit through loss, reinforcing collective moral values. This study confirms the cross-cultural applicability of Freytag's Pyramid, demonstrating that indigenous oral narratives possess sophisticated and systematic plot structures comparable to Western dramas. It provides a robust literary framework for analyzing traditional performances, thereby legitimizing Opera Batak as a valuable object of academic inquiry and contributing to the broader field of comparative narrative studies.